TUMEFACCION EXPERIMENTAL DEL CEREBRO IV CIRCULACION CEREBRAL - PI SUNER, JAIME; ALCALDE OBRADOR, S (Instituto de Salubridad Publica Enfermedades Tropicales, CD MEXICO, DF, MEX, 1943)
In dogs the water content of cerebral tissue with tumefaction produced by exptl lesion of the 4th ventricle was 798% for the gray matter and 688% for the white matter This is identical with the water content following intraven injus of large quantit
BOL INST ESTUD MED BIOL
Keywords: TUMEFACCION, EXPERIMENTAL, CEREBRO; CIENCIAS MEDICAS; MEDICINA INTERNA; NEUROLOGIA